The benefits and impacts of e-learning and barriers to diffusion in higher education in Hong Kong: through the eyes of teachers and researchers - Wong, Andrew Lap Sang (2013)
Hong Kong, a populated city, meets all the necessary technological and economic conditions for e-learning to be thriving in higher education. However, online survey results of students and teachers of a major tertiary educational institution over a period of three years showed that e-learning is not nearly as popular as anticipated and traditional face-to-face learning remains the preferred mode of study. Are the benefits and impact experienced in other countries equally applicable to Hong Kong? What are the barriers to e-learning diffusion in Hong Kong? Answers to these questions were sought from the teachers and researchers of e-learning in Hong Kong higher education.